Biochar in the Remediation of Organic Pollutants in Water: A Review of Polycyclic Aromatic Hydrocarbon and Pesticide Removal - Jelena Beljin; Nina Đukanović; Jasmina Anojčić; Tajana Simetić; Tamara Apostolović; Sanja Mutić; Snežana Maletić (Nanomaterials)
This review explores biochar’s potential as a sustainable and cost-effective solution for remediating organic pollutants, particularly polycyclic aromatic hydrocarbons (PAHs) and pesticides, in water. Biochar, a carbon-rich material produced from biomass pyrolysis, has demonstrated adsorption efficiencies exceeding 90% under optimal conditions, depending on the feedstock type, pyrolysis temperature, and functionalization. High surface area (up to 1500 m2/g), porosity, and modifiable surface functional groups make biochar effective in adsorbing a wide range of contaminants, including toxic metals, organic pollutants, and nutrients. Recent advancements in biochar production, such as chemical activation and post-treatment modifications, have enhanced adsorption capacities, with engineered biochar achieving superior performance in treating industrial, municipal, and agricultural effluents. However, scaling up biochar applications from laboratory research to field-scale wastewater treatment poses significant challenges. These include inconsistencies in adsorption performance under variable environmental conditions, the high cost of large-scale biochar production, logistical challenges in handling and deploying biochar at scale, and the need for integration with existing treatment systems. Such challenges impact the practical implementation of biochar-based remediation technologies, requiring further investigation into cost-effective production methods, long-term performance assessments, and field-level optimization strategies. This review underscores the importance of addressing these barriers and highlights biochar’s potential to offer a sustainable, environmentally friendly, and economically viable solution for large-scale wastewater treatment.